Analisi Pengaruh Modal, Tenaga Kerja dan Bahan Baku terhadap Tingkat Produksi Pada Industri Batu Bata di Desa Pene Kecamatan Jerowaru Kabupaten Lombok Timur: Analysis of the Influence of Capital, Labor and Raw Materials on Production Levels in the Brick Industry in Pene Village, Jerowaru District, East Lombok Regency - M. Ali Karmani (Pendidikan Al-Gafari, 2025)
The industrial sector is one of the hopes in improving the community's economy because it affects other sectors. Every activity carried out by a company or organization including agro-industrial businesses has the main goal of achieving maximum profit. The purpose of this study was to determine and analyze the influence of capital, labor and raw material production factors on brick production in the brick industry in Pene Village, Jerowaru District, East Lombok Regency. The data used in the study were primary data and secondary data. Primary data were obtained from direct interviews with business respondents in the brick industry in Pene Village, Jerowaru District, East Lombok Regency. The analysis tool used in this study was a multiple linear regression model. The results of the linear regression calculation showed that partially and simultaneously or together the variables of capital, labor and raw materials had a positive and significant influence on the amount of brick production in Pene Village, Jerowaru District, East Lombok Regency. Where simultaneously using the F test with a confidence level of 95%, the calculated F value was obtained > F table, namely the calculated F of 8932.215 and the F table of 2.82. While partially or individually using the T test with a confidence level of 95%, obtained T count table 2.015 and T count for capital 2.630, labor 0.537, raw materials 111.034, from this it is concluded that T count is greater than T table. In addition, the three variables included in the model are all significant as seen from the probability of the three far below 0.05, which is 0.000. Thus the alternative hypothesis is accepted while the null hypothesis (Ho) is rejected.